Analisis Kinerja Mesin Sterilizer (Rebusan) Menggunakan Metode Overall Equipment Effectiveness (OEE) di PTPN V Sei Buatan - Satriardi, Satriardi; Kholid Darmawan, Bagus; Denur, Denur (Fakultas Teknik UMRI, 2024)
Sterilizer (boiling) machines are important in palm oil production in the palm oil processing industry. This study analyzes the performance at PTPN V Sei Buatan using the Overall Equipment Effectiveness (OEE) method. Observation and production data were used to calculate OEE, showing that the machine experienced significant downtime and low performance efficiency and product quality. Improvement recommendations, including routine maintenance, better maintenance scheduling, and operator training, are proposed to improve machine performance. The OEE method helps identify areas of improvement to increase operational efficiency and productivity at PTPN V Sei Buatan.